Penyuluhan dan Penanaman Mangrove di Sungai Merambai Dalam Rangka Memperingati Hari Mangrove Sedunia - Fitri Dewi; Nuranisa Nuranisa; Gorby Sergeyevich Muhammad Rasyid; Betha Anjela; Nopriansyah Nopriansyah; Neni Hermita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
In commemoration of world mangrove day, the real working lecture team integrated abdimas University of Riau conducted mangrove extension and planting. This extension was conducted on July 26, 2021 located in Merambai River Teluk Belitung, Belitung Bay Village, Merbau Subdistrict, Meranti Islands Regency. This activity aims to provide knowledge and understanding to children about the important role of mangrove forests for human life. The main target of this extension activity is children educated at dawn in the village. The method used in this extension method is a method of lectures, and discussions, visits to mangrove planting sites. The lecture method is used to convey information about mangroves. Visits to mangrove planting locations are intended to conduct direct planting according to information that has been submitted previously